Specific Antidotes for Direct Oral Anticoagulants in Life-Threatening Bleeding - A. B. Sumarokov; L. I. Buryachkovskaya; N. V. Lomakin (Столичная издательская компания, 2019)
Review presents data on medicines from the new group of cardiovascular drugs, direct oral anticoagulants (DOACs) inhibitors, as antidotes for DOAC when stopping life-threatening bleeding. DOAC therapy is accorded by hemorrhages with lower frequency than therapy by indirect anticoagulants, but really exist. New antidotes for DOACs are idarucizumab, andexanet, ciraparantag. The need in antidotes for DOAC may suddenly appear in spontaneous bleeding, during surgical operation, invasive procedure, due to trauma, in patients with stroke, kidney or liver failure. Data is given on the frequency of the main types of bleeding while taking new oral anticoagulants. Information concerning use of antidotes for DOACs in bleedings as well as use of non-specific therapy are reviewed.